Before pornography : erotic writing in early modern England - Moulton, Ian Frederick, 1964- (Studies in the history of sexuality., 2000)
Before Pornography explores the relationship between erotic writing, masculinity, and national identity in Renaissance England. Drawing on both manuscripts and printed texts, and incorporating insights from modern feminist theory and queer studies, the book argues that pornography is ahistorical phenomenon: while the representation of sexual activity exists in nearly all cultures, pornography does not. The book includes analyses of the social significance of eroticism in such canonical texts as Sidney's Defense of Poesy and Spenser's Faerie Queene.